Sabellid worms from the Patagonian Shelf and Humboldt Current System (Annelida, Sabellidae): Phyllis Knight-Jones’ and José María Orensanz’s collections - Tovar-Hernández, María Ana; de León-González, Jesús Ángel; Bybee, David R. (Zootaxa, 2017)
The South American sabellid polychaete worm collections of Phyllis Knight-Jones and José María Orensanz were recovered, curated and specimens identified, comprising fourteen species grouped in nine genera. Five species belonging to the genera Chone Krøyer, 1856, Acromegalomma Gil and Nishi, 2017, Notaulax Tauber, 1879, Parasabella Bush, 1905, and Pseudopotamilla Bush, 1905, are described as new to science from the Patagonian Shelf (Argentina). Jasmineira crumenifera Hartmann-Schröder, 1986, Myxicola sulcata Ehlers, 1912, Parasabella columbi (Kinberg, 1867), Perkinsiana antarctica (Kinberg, 1867) and Perkinsiana assimilis (McIntosh, 1885) are redescribed and reported from several Patagonian localities. Three new combinations are made: Sabella tilosaula Schmarda, 1861, is transferred to Notaulax, Sabella magalhaensis Kinberg, 1867, to Perkinsiana Knight-Jones, 1983, and Potamilla platensis Hartman, 1953, to Pseudopotamilla. Potamethus littoralis Hartman, 1967, was synonymized with Perkinsiana magalhaensis. Notaulax tilosaula, Perkinsiana antarctica and P. magalhaensis are reported from the biogeographical subregion Humboldt Current System, whereas Bispira sp., Chone orensanzi sp. nov., Jasmineira crumenifera, Acromegalomma schwindtae sp. nov., M. sulcata, Notaulax salazari sp. nov., Parasabella columbi, P. yonowae sp. nov., Perkinsiana assimilis, Pseudopotamilla platensis, and P. knightjonesae sp. nov., are reported from the Patagonian Shelf.